Comparative behavior of red lionfish (Pterois volitans) on native and Pacific vs. invaded Atlantic coral reefs - Cure, K.; Benkwitt, C.; Kindinger, T.; Pickering, E.; Pusack, T.; McIlwain, Jennifer; Hixon, M. (Marine Ecology Progress, 2012)
Pacific red lionfish Pterois volitans have invaded Atlantic reefs and reached much greater population densities than on native reefs. We hypothesized that lionfish on invaded reefs would (1) experience higher kill rates and thus spend less time hunting, given the naïveté of Atlantic prey, (2) consume a greater variety of prey, given the lack of native prey defenses, and (3) display less pronounced crepuscular patterns of hunting, given the ease of capturing Atlantic prey. Comparative behavioral observations were conducted in 2 native regions (Philippines and Guam) and 2 invaded regions (Cayman Islands and Bahamas) to assess lionfish time budgets and diurnal activity patterns and to explore correlations between environmental variables and lionfish behavior. Contrary to our first hypothesis, total time allocated to hunting and kill rates showed no difference between native and invaded reefs, despite considerable regional variation. However, Atlantic prey of lionfish were twice as large as Pacific prey, suggesting that despite similar hunting behavior, invasive lionfish ingest greater daily rations of prey biomass. Furthermore, consistent with our second hypothesis, lionfish on invaded reefs had broader diets, and also relied less on ‘blowing’ behavior for prey capture, pointing to substantial prey naïveté in the invaded range. Importantly, only in the invaded range did we observe lionfish consuming parrotfishes, the decline of which could have indirect effects on interactions between seaweeds and corals. Finally, lionfish overall tended to exhibit a crepuscular pattern in behavior whereby hunting peaked at sunrise and/or sunset, with no differences attributable to native vs. invasive status.